Stability of cypermethrin against a prepared high surface area magnesium oxide [compact disc] - 241219 Hanis Mohd. Yusoff (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Kimia))- Universiti Teknologi Malaysia, 2006